Influence of temperatures on structure, thermoelectric, and mechanical properties of nanocrystalline SnSe thin films deposited by thermal evaporation. (August 2022) - Singh, Komal; Soni; Anwar, Sharmistha; Dubey, Paritosh; Mishra, Suman K.
Abstract: The Tin Selenide (SnSe) thermoelectric materials' high heat-electricity inter-conversion capability makes it a potential energy resource material to tap the waste heat from different industrial processing. The present work has optimized parameters for the deposition of single-phase nanocrystalline SnSe thin films using the thermal evaporation technique. The XRD, Raman Spectroscopy, SEM, EDS, Seebeck Coefficient, Electrical Conductivity, and Thermal Conductivity data analyses were used to optimize and establish the structure-thermoelectric property relationship for nanocrystalline SnSe films. The phase analysis of the SnSe thin films deposited at various substrate heating temperatures (Ts ) reveals a significant influence of Ts in the evolution of a single phase of SnSe film. The films deposited at Ts ≤ 200 °C evolved with the phases of Sn, Se, and SnSe, whereas films deposited at Ts ≥ 300 °C grew with single-phase polycrystalline SnSe. An increase in crystallite size with a shape transformation from circular to elongated grains was observed with Ts . The maximum ZT value of 0.64 with a power factor value of ~2.2 μWcm -1 K -2 at 750 K measuring temperature (Ta ) was obtained for the SnSe film deposited at Ts = 300 °C. The change in thermoelectric properties with Ta, including a p-type to n-type transition observed at ~600 K, was correlated with the alteration of structure and the elemental composition of the deposited films after heating at 350 °C. The heating temperature significantly influenced the hardness and elastic modulus values of the films deposited at Ts ≤ 300 °C. Graphical Abstract: ga1 Highlights: Thermoelectric SnSe thin films were grown over the glass by thermal evaporation. Single-phase nanocrystalline SnSe thin films were obtained at Ts ≥ 300 °C. Thermoelectric properties of the deposited SnSe films were measured up to 750 K. Structural and compositional stabilities were examined with heating temperature. Establish the structure-thermoelectric property relationship for the SnSe films.